HUBUNGAN ANTARA KINERJA DOKTER DENGAN TINGKAT KEPUASAN PASIEN DI POLIKLINIK PENYAKIT DALAM RUMAH SAKIT AISYIYAH SITI FATIMAH TULANGAN SIDOARJO - Karimah Hasni, Nur; Priambodo, Tjatur; Ghufron, Musa (JurnalMU: Jurnal Medis Umum, 2025)
Patient satisfaction is one of the main elements of hospital services, with doctors' performance being a key factor in determining patient satisfaction. This study aims to analyze the relationship between doctors' performance and patient satisfaction levels in the Internal Medicine Polyclinic of RSA Fatimah Sidoarjo. The research employed a quantitative method with an analytical observational design and a cross-sectional approach. Data were collected through questionnaires using a simple random sampling technique, involving 99 patients as respondents. Overall, the respondents were predominantly female, aged over 55 years, with elementary school as their highest level of education, employed as members of the military/police or unemployed, and primarily covered by BPJS for healthcare costs. Data analysis using the Spearman correlation test showed a p-value < 0.001 across five dimensions of patient satisfaction (tangible, reliability, responsiveness, assurance, and empathy), indicating a significant relationship between doctors' performance and patient satisfaction. Doctors' performance was rated as excellent (total Likert scale score = 360), and patient satisfaction was categorized as very satisfied across all dimensions, with the highest score in the assurance dimension (total Likert scale score = 357). Keywords: doctors' performance, patient satisfaction, polyclinic